Antibacterial Activity of Jackfruit Leaf (Artocarpus Heterophyllus LMK.) Ethanol Extract Gel on Propionibacterium acnes - Fitrya, Fitrya; Apriani, Elsa Fitria; Ahmadi, Adik; Wijaya, Dina Permata; Nurain, Khazanah (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2023)
Introduction: Artocarpus heterophyllus LMK. leaves contain flavonoids, tannins, and saponins, which have the potential to be antibacterial. Aims: This study aims to test the antibacterial activity of A. heterophyllus leaves ethanol extract, which is formulated in a gel preparation. Methods: Antibacterial testing was done on the acne-causing bacteria Propionibacterium acnes. The gel formula is designed with an extract concentration of 5, 10, or 15% with Carbopol 940 and HPMC as the bases. The antibacterial activity test was carried out using the well diffusion method. Result: The results of the study showed that the concentration of the extract affected pH, adhesive power, removability, and viscosity. Antibacterial activity tests showed that the gel of A. heterophyllus extract could inhibit Propionibacterium acnes bacteria. The higher the concentration of the extract, the greater the antibacterial activity. Conclusion: It can be concluded that the gel with an extract concentration of 15% gave the strongest antibacterial activity with an inhibition zone of 10.9 ± 1.18 mm.